Geometric model for computer graphics : Disk and Ball B-Spline - Seah, Hock Soon. (2008)
Technology plays an important role in creation of arts, animation and game. The geometric model proposed here is a novel and advanced modeling and animation technology based on Disk and Ball B-Spline (DBBS).